Faktor-faktor Lingkungan Meningkatkan Insidensi Demam Berdarah di Sulawesi Selatan - Musdalifah Syamsul (Sarana Ilmu Indonesia (salnesia), 2019)
Dengue fever is an increasing public health problem in South Sulawesi, Indonesia. The Dengue endemic area and dengue fever cases occur for the last 3 years is Maros Regency. The purpose of this study was to conduct a study of the relationship of environmental factors with the incidence of dengue in Maros Regency. Type of analytic research with cross sectional study approach. The number of subject in this study was 112 subjects. Data collection through interview using questioner. Data analysis using chi square statistical test. The result showed there is no relation of incidence of dengue fever disease with water management with p value=0.501, waste management with p value=0.000 have relationship with dengue fever incidence. Therefore, it is hoped that the related parties should improve health education and provide waste bins.